The Effect of Intermittent High-Intensity and Continuous Moderate-Intensity Exercises on CTRP-1, CTRP-5 and CTRP-15 Values in Rats Fed with a High-Fat Diet - Mostafa Fahmi Alsediri; Keyvan Sharifmoradi; Mousa Khalafi; Zahra Pezeshki (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  The effect of high-intensity interval training and moderate-intensity continuous training on CTRPs under dietary Intake is unclear. So, the aim of the present study was to investigate the effect of high-intensity interval training (HIIT) and moderate intensity continuous training (MICT) on protein levels of CTRP-1, CTRP-5, and CTRP-15 in rats fed a high-fat diet. Materials & Methods: This study was experimental in nature, utilizing a post-test design with a control group. Twenty-four male Wistar rats were randomly divided into four equal groups, including standard diet (6), high-fat diet (6), high-fat diet with high-intensity interval training (6), and high-fat diet with moderate intensity continuous training (6). The HIIT and MICT groups did their own group-specific exercise for 8 weeks, 5 sessions per week. To measure the protein levels of CTRP-1, CTRP-5, and CTRP-15 using the western blot method. were used. Statistical analysis was performed using SPSS V.26; one-way analysis. of variance and Tukey's post hoc test were used to analyze data at a significance level less than 0.05. Results: In the HFD group, visceral fat levels of CTRP-1, CTRP-5, and CTRP-15 went up significantly (P<0.001) after eight weeks of the diet. A lot less CTRP-1, CTRP-5, and CTRP-15 visceral fat was found in the MICT group compared to the HFD group (P<0.001). The HIIT protocol also greatly lowered the amount of CTRP-1 protein in visceral fat compared to the ND group (P=0.001). Conclusion: While exercise training can prevent the effects of a high-fat diet, moderate-intensity exercise training is a more effective approach. A high-fat diet is associated with a significant increase in CTRPs of visceral fat.